Communication during Covid‐19: Use of video conferencing technology by people living with dementia. (1st February 2022) - Agustus, Jennifer L; Volkmer, Anna; Jeong, Tina Hyerim; Jiang, Jessica; Brotherhood, Emilie V; Dobson, Lucianne; Harding, Emma; Gonzalez, Aida Suarez; Crutch, Sebastian J; Warren, Jason D; Hardy, Chris JD
Abstract: Background: The use of videoconferencing technology has increased as an alternative communication method for people to retain social and clinical contact during Covid‐19 restrictions. This study investigated the uptake, limitations and benefits of videoconferencing for people living with dementia (PLWD). Method: Twenty‐three PLWD, 87 caregivers (on behalf of PLWD) and 39 healthy control participants anonymously reported their experiences of using videoconferencing technology during the Covid‐19 pandemic (PLWD: 38‐90 years; controls: 32‐100 years). The online survey ran between December 2020 and April 2021. Respondents represented experiences of people living with Alzheimer's Disease (AD; 27), Frontotemporal Dementia (FTD; 23), Primary Progressive Aphasia (PPA; 24), Posterior Cortical Atrophy (PCA; 22), Lewy Body Dementia (LDB; 7). Mann‐Whitney U tests were used to compare Likert ratings of videoconferencing experiences between PLWD or diagnostic subgroups and controls. Result: The majority of survey respondents that use videoconferencing technology reported an increased usage during the Covid‐19 pandemic than before (85%). However, 28% of PLWD did not use videoconferencing at all, compared to 3% of healthy controls. Only 53% of PLWD reported they liked using videoconferencing technology compared to 67% of controls, and this was lowest for people with LBD (33%) or PCA (40%). Interestingly, 64% of people with FTD liked videoconferencing and rated it more engaging than traditional telephone calls compared to healthy controls (p=0.045). People with AD, PCA and FTD found online meetings with multiple people more difficult than controls (p=0.036; p<0.001; p=0.030). Qualitative responses to questions on telemedicine were mixed, with PLWD three times more likely to report overall negative consequences (e.g. "communication better face‐to‐face") than positive benefits (e.g. "less tiring") for cognitive clinic and dementia‐related GP appointments, compared to face‐to‐face visits. Conclusion: The use of videoconferencing by PLWD and healthy controls has increased during the Covid‐19 pandemic. However, a significant proportion of PLWD surveyed are not able to use these technologies, with different profiles of uptake and enthusiasm across dementia subtypes. Our findings suggest that whilst representing a helpful alternative to face‐to‐face communication during the pandemic, videoconferencing (particularly in clinical settings) may be a significant barrier to communication for some people with cognitive impairment.